Pengaruh Penggunaan Peningkat Penetrasi Propilen Glikol terhadap Laju Difusi Polifenol dalam Gel Ekstrak Kulit Buah Naga Merah (Hylocereus polyrhizus) - Tasman, Rahmat Setiady; Arisanty, Arisanty; Stevani, Hendra (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2023)
Polyphenols contained in the skin of red dragon fruit are efficacious as antioxidants which can be used as topical preparations. Polyphenols are polar, making it difficult to penetrate through the stratum corneum of skin which is rich in lipids. The way that can be done to increase the rate of drug penetration through the skin is the addition of a propylene glycol penetration enhancer. The purpose of this study was to determine the effect of adding propylene glycol as a penetration enhancer on the diffusion rate of polyphenols from red dragon fruit peel extract gel. This type of research was experimental by testing the physical quality of red dragon fruit skin extract gel preparations using the accelerated stability test method and penetration-diffusion testing. Gel preparations were made in 4 formulas with varying concentrations of propylene glycol 5% (F1), 7.5% (F2), 10% (F3) and negative control without propylene glycol. The results showed that all formulas met the physical quality test requirements. Then a penetration test was carried out using a Franz diffusion cell for 4 hours with a phosphate buffer diffusion medium pH 7.4. Polyphenol equivalence treatment was carried out by spectrophotometry. The cumulative amount of polyphenols that diffuses through the membrane after 4 hours is 176.15 µg/cm2 for (F1), 232.76 µg/cm2 for (F2), 239.67 µg/cm2 for (F3) and 126.45 µg/cm2 for (F0). This study concludes that varying the concentration of the penetration enhancer propylene glycol has an effect on the diffusion rate of polyphenols from red dragon fruit skin extract gel preparations, with formula 3 producing the greatest diffusion rate effect.